Journal of Evolution Equations - Arendt, Wolfgang; Pierre, Michel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Birkhäuser.)
The Journal of Evolution Equations (JEE) publishes high-quality, peer-reviewed papers on equations dealing with time dependent systems and ranging from abstract theory to concrete applications. Research articles should contain new and important results. Survey articles on recent developments are also considered as important contributions to the field. Particular topics covered by the journal are: Linear and Nonlinear Semigroups Parabolic and Hyperbolic Partial Differential Equations Reaction Diffusion Equations Deterministic and Stochastic Control Systems Transport and Population Equations Volterra Equations Delay Equations Stochastic Processes and Dirichlet Forms Maximal Regularity and Functional Calculi Asymptotics and Qualitative Theory of Linear and Nonlinear Evolution Equations Evolution Equations in Mathematical Physics Elliptic Operators Bibliographic Data J. Evol. Equ. First published in 2001 1 volume per year, 4 issues per volume approx. 1200 pages per volume Format: 15.5 x 23.5 cm ISSN 1424-3199 (print) ISSN 1424-3202 (electronic) AMS Mathematical Citation Quotient (MCQ): 0.82 (2018).
Keywords: Mathematical analysis; Analysis (Mathematics).; Analysis